Two Polarities of Attention in Social Contexts: From Attending-to-Others to Attending-to-Self - Kuang, Shenbing (Frontiers in Psychology, 2016)
Social attention is one special form of attention that involves the allocation of limited processing resources in a social context. Previous studies on social attention often regard how attention is directed toward socially relevant stimuli such as faces and gaze directions of other individuals. In contrast to attending-to-others, a different line of researches has shown that self-related information such as own face and name automatically captures attention and is preferentially processed comparing to other-related information. These contrasting behavioral effects between attending-to-others and attending-to-self prompt me to consider a synthetic viewpoint for understanding social attention. I propose that social attention operates at two polarizing states: In one extreme, individual tends to attend to the self and prioritize self-related information over others', and, in the other extreme, attention is allocated to other individuals to infer their intentions and desires. Attending-to-self and attending-to-others mark the two ends of an otherwise continuum spectrum of social attention. For a given behavioral context, the mechanisms underlying these two polarities will interact and compete with each other in order to determine a saliency map of social attention that guides our behaviors. An imbalanced competition between these two behavioral and cognitive processes will cause cognitive disorders and neurological symptoms such as autism spectrum disorders and Williams syndrome. I have reviewed both behavioral and neural evidence that support the notion of polarized social attention, and have suggested several testable predictions to corroborate this integrative theory for understanding social attention.